Game Design Jomblo Keren As a Startup Marketing Product - Celvin Laviano; Ridwan Sanjaya; Hendra Prasetya (Soegijapranata Catholic University, 2017)
The number of competitors makes the competition in the game industrymore difficult if not able to read opportunities well. Because it takes theability to be able to take advantage of opportunities with the best. Bill Gates once quoted a word from Don Corleone that we must keep our friend close but our enemies even closer. Because of these competitors we will see various types of opportunities and opportunities that exist. The creation of